Toxocariasis in a Child with Autism Spectrum Disorder - Pieroni, Filippo (Int J Environ Res Public Health, 2021)
A boy affected by autism spectrum disorder was admitted for persistent high fever, without shiver, for two weeks. The boy referred to abdominal pain, in the first week of fever, and to mild anorexia in the last days before admittance to our hospital centre. The father reported that the boy suffered by geophagia and coprophagia and he has been going to a didactical farm (where he has been exposed to several kinds of animals) to improve his neuropsychiatric condition. Blood analysis shows severe eosinophilia and high levels of total IgE, and abdominal echocardiography showed hepatic lesions. Enzyme-linked immunosorbent assay (ELISA) and Western blot (WB) confirmed the suspicion of toxocariasis, linked to the habit of the boy to ingest ground or animal faeces in a didactic farm frequented by the boy. Treatment with albendazole and prednisone was administered with a rapid improvement of the symptoms and the laboratory findings and significant reduction of the hepatic lesion.